Some recent advances in mathematics and statistics proceedings of Statistics 2011 Canada/IMST 2011-FIM XX, Montreal, Canada, 1-4 July 2011 - Chaubey, Yogendra P. (World Scientific, 2013)
"The present volume consists of 19 papers dealing with current issues in mathematical and statistical methods that were presented at Statistics 2011 Canada Conference in Applied Statistics that was held together with the 20th conference of the Forum for Interdisciplinary Mathematics titled, "Interdisciplinary Mathematical & Statistical Techniques" from July 1 to July 4, 2011."--Preface.